2022
DOI: 10.1007/s00125-022-05797-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen rapidly improves tissue-specific insulin sensitivity and mitochondrial capacity in humans with type 2 diabetes: a randomised placebo-controlled crossover trial

Abstract: Aims/hypothesis Hyperbaric oxygen (HBO) therapy may improve hyperglycaemia in humans with type 2 diabetes, but underlying mechanisms are unclear. Our objective was to examine the glucometabolic effects of HBO on whole-body glucose disposal in humans with type 2 diabetes. Methods In a randomised placebo-controlled crossover trial located at the German Diabetes Center, 12 male individuals with type 2 diabetes (age 18–75 years, BMI <35 kg/m2, HbA1c 42–75 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Hepatic H2O2 emission was assessed fluorimetrically by using Amplex Red in isolated mitochondria [14]. Thiobarbituric acid reactive substances (TBARS) were assessed fluorometrically in liver samples (BioTek, Bad Friedrichshall, Germany) [21,27]. Catalase activity was measured colorimetrically in liver tissue lysates (Cayman Chemical Company, Ann Arbor, Michigan, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Hepatic H2O2 emission was assessed fluorimetrically by using Amplex Red in isolated mitochondria [14]. Thiobarbituric acid reactive substances (TBARS) were assessed fluorometrically in liver samples (BioTek, Bad Friedrichshall, Germany) [21,27]. Catalase activity was measured colorimetrically in liver tissue lysates (Cayman Chemical Company, Ann Arbor, Michigan, United States).…”
Section: Methodsmentioning
confidence: 99%
“…There was no association between these disturbances and the amount of insulin administered suggesting that the degree of insulin resistance varied between patients and even within individual patients. There was no evidence that higher doses of insulin (up to 10U/kg/h) were associated with more adverse effects that low doses [56] A rapid and marked increase in mitochondrial function and ATP production also resulted from another example of increased fuel availability in the form of 2 hours of hyperbaric oxygen in type 2 diabetic subjects [57].…”
Section: High Dose Insulinmentioning
confidence: 99%
“…Meanwhile, Lecoultre [ 247 ] et al found that exposure to moderate hypoxic (15 ± 0.5% O 2 , ~2400 m altitude) for 10 consecutive nights in obese men (a within-group comparison without controls) increased insulin sensitivity. Some studies also found that for type 2 diabetes patients, peripheral insulin sensitivity increased during hyperbaric oxygen treatment (HBOT), and this increase was maintained for 30 min after HBOT [ 248 , 249 , 250 ].…”
Section: Application Of Hypoxic Exercise In Treatment Of Metabolic Di...mentioning
confidence: 99%